Hubungan Kepatuhan Prosedur Tetap Perawatan Ulkus Diabetikum dengan Kepuasan Pasien Diabtes Melitus Pengguna BPJS PBI di RSUD Sleman - Widuri Widuri; Dwi Agustiana Sari; Akhmad Faisal (Journal of Health (JoH), 2016)
Background: Satisfaction is the degree of one's feelings after comparing the performance or results which felt with expectations. In this case the patient satisfaction as a benchmark the quality of Sleman hospital where the vision and mission is a quality health service delivery. Especially for compliance using SOP, the Sleman hospital is part of the process of achieving Satisfaction Patient Diabetes Mellitus User BPJS PBI at Sleman Hospital. Objective:Knowing the relationship between compliance procedures care diabetic ulcers with satisfaction the patient diabetes mellitus user BPJS PBI at Sleman Hospital. Methods:This research is research non experiment using the design descriptive correlative.This research was at Sleman Hospital, from May to July. With the methods samples being used were a total of sampling and the number of samples in this research is 26 of respondents. Result:Of the 26 respondents there are as many as 23 nurses (88.5%) carry out the action in accordance with procedures still make a high percentage of the level of satisfaction. Conclusions:There is a correlation between compliance procedures care diabetic ulcers with satisfaction the patient diabetes mellitus user BPJS PBI at Sleman Hospital,with the result Asymp.Sig(2-sided)0,001<0,05.